A discussion of microbial genetics in fermentation process development with particular reference to fungi producing high yields of antibiotics - Ball, C (Folia microbiologica, 1980)
When trying to improve antibiotic processes that are already high yielding, real industrial problems have to be faced. These include the use of organisms with non-ideal growth and recombination cycles, and problems of scale up from the laboratory to the main production plant. Many of the principles derived from academic studies have to be radically modified before they can be applied in the industrial context. These issues are a challenge to those who genuinely wish to contribute to the solution of industrial problems.
Keywords: mutace; geny; genetické inženýrství; Fungi; Genetic Engineering; Fermentation; Recombination, Genetic; Industry; antibakteriální látky; průmysl; rekombinace genetická; Anti-Bacterial Agents; Genetics, Microbial; houby; Mutation; fermentace; mikrobiální genetika; Genes